Molecular analysis of integrons and antimicrobial resistance profile in Shigella spp. isolated from acute pediatric diarrhea patients - Soltan Dallal, Mohammad Mehdi; Omidi, Sajjad; Douraghi, Masoumeh; Haghi Ashtiani, Mohammad Taghi; Sharifi Yazdi, Mohammad Kazem; Okazi, Arash (German Medical Science GMS Publishing House, 2018)
Introduction: spp. is a growing global health concern due to increasing multiple drug resistance, commonly resulting in therapeutic failure. Integrons are gene expression systems run by integrase genes. The aims of this study were detection of class I, II and III integrons and assessment of antimicrobial resistance in spp. isolated from acute pediatric diarrhea patients.Materials and methods: From January to December 2015, were isolated from 310 non-duplicative diarrheal stool samples in Children's Medical Center, Tehran, Iran. The isolates were analyzed for their antibiotic susceptibility using CLSI guidelines Multiplex PCR was used for amplification of I, II and III integron-associated integrase () genes.Results: Of 310 stool samples, 16 (5.2%) were positive for in 7 of them and in 9 of them were identified. Results of the antimicrobial susceptibility test showed that 6.2%, 50%, 31.2%, 6.2%, 81.2%, 56.2% and 31.2% of the isolates were resistant to gentamicin, chloramphenicol, nalidixic acid, ciprofloxacin, tetracycline, ampicillin and trimethoprim-sulfamethoxazole, respectively. Multiplex PCR results revealed that 6.2% (1/16), 31.2% (5/16), 50% (8/16) of isolates carried I, iII and both I/lI genes. No class were detected.Discussion: In this study, multidrug resistance was seen in isolates similar to that in isolates from other geographical areas. This is possible due to inappropriate use of antimicrobials. Furthermore, prevalence of multidrug resistance was significantly linked to the presence of integrin genes. Conclusion: A class 2 integron plays a role in presence of multidrug resistance in spp. It is vital to prevent the spread of antibiotic resistance through continuous monitoring.